ANALISIS PENATAAN RUANG TERBUKA HIJAU DI KOTA PEKANBARU - Ardiansah, Ardiansah; Oktapani, Silm (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2019)
Thearrangement of the green open space of the City of Pekanbaru has not been implemented as mandated by the Law on Spatial Planning. Because the rapid development of malls and offices is not comparable to the construction of green open spaces. This research is categorized as sociological legal research, namely research on the effectiveness of law in the community. The results of the study show that the Pekanbaru City Government has not yet fully organized and utilized green open space land. The barriers are structured due to the weak ability to control the land, limited funds, the absence of green open space planning, low private participation, low public awareness, expensive land prices, the ability of the government to only buy land according to the Tax Object Value, and not yet effective implementation of the green open space program. Regulatory efforts include preparing green open space, providing funding, collaborating with the private sector, limiting the construction of buildings and buildings, cooperating with investors, making regulations with strict sanctions on the conversion of green open spaces, synergies between government, the private sector, and community and a strategy for structuring green open space. The Pekanbaru City Government needs to show a strong commitment in structuring green open space.